2010
DOI: 10.1074/jbc.m109.092759
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Survival Signaling Is Blocked by Anti-β2-microglobulin Monoclonal Antibody via a MAPK/Lipogenic Pathway in Human Prostate Cancer Cells

Abstract: A new cis-acting element, sterol regulatory element-binding protein-1 (SREBP-1) binding site, within the 5-flanking human androgen receptor (AR) promoter region and its binding transcription factor, SREBP-1, was identified to regulate AR transcription in AR-positive human prostate cancer cells. We further characterized the molecular mechanism by which a novel anti-␤2-microglobulin monoclonal antibody (␤2M mAb), shown to induce massive cell death in a number of human and mouse cancer cell lines, interrupted mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 53 publications
2
63
0
Order By: Relevance
“…As we summarized previously (Shiota et al 2011b (Mizokami et al 1994), and Foxo3a (Yang et al 2005), regulate AR expression. In addition, it has recently been shown that the SREBP-1 transcription factor regulates AR expression (Huang et al 2010), is overexpressed during progression to castration resistance (Ettinger et al 2004), regulates lipogenesis, and induces oxidative stress via NADPH oxidase 5 (Nox5) expression that can be reversed by the Nox inhibitor diphenyliodonium (DPI). Intriguingly, AR expression was shown to be repressed by DPI, indicating that AR expression by SREBP-1 may be mediated by the Nox pathway .…”
Section: Ar Overexpressionmentioning
confidence: 99%
“…As we summarized previously (Shiota et al 2011b (Mizokami et al 1994), and Foxo3a (Yang et al 2005), regulate AR expression. In addition, it has recently been shown that the SREBP-1 transcription factor regulates AR expression (Huang et al 2010), is overexpressed during progression to castration resistance (Ettinger et al 2004), regulates lipogenesis, and induces oxidative stress via NADPH oxidase 5 (Nox5) expression that can be reversed by the Nox inhibitor diphenyliodonium (DPI). Intriguingly, AR expression was shown to be repressed by DPI, indicating that AR expression by SREBP-1 may be mediated by the Nox pathway .…”
Section: Ar Overexpressionmentioning
confidence: 99%
“…SREBPs can reciprocally activate the expression of AR via binding to an SRE in the 5′-untranslated region of the AR gene (Fig. 2) (Huang et al 2010), and modulation of SREPB1 activity has parallel effects on AR expression and function (Fig. 2) .…”
Section: :5mentioning
confidence: 99%
“…Recent studies have demonstrated that tumor cells treated with antibodies specific for β2M or MHC class I molecules undergo apoptosis in vitro and in vivo (in a mouse model). These findings suggest that targeting of either β2M or MHC class I offers a potential therapeutic approach for the treatment of β2M/MHC class I-expressing malignancies (Cao et al, 2011;Huang et al, 2010;Shi et al, 2009;Triozzi et al, 2013;Yang and Yi, 2010). However, the specific function of β2M in modulating tumorigenesis is poorly understood.…”
Section: Discussionmentioning
confidence: 97%